A Critical Study of the Effect of Polymeric Fibers on the Performance of Supported Liquid Membranes in Sample Microextraction for Metals Analysis - Rafael J. González-Álvarez; José A. López-López; Juan J. Pinto; Carlos Moreno (Membranes, 2020)
Popularity of hollow fiber-supported liquid membranes (HF-SLM) for liquid-phase microextraction (HF-LPME) has increased in the last decades. In particular, HF-SLM are applied for sample treatment in the determination and speciation of metals. Up to the date, optimization of preconcentration systems has been focused on chemical conditions. However, criteria about fiber selection are not reflected in published works. HFs differ in pore size, porosity, wall thickness, etc., which can affect efficiency and/or selectivity of chemical systems in extraction of metals. In this work, Ag+ transport using tri-isobutylphosphine sulfide (TIBPS) has been used as a model to evaluate differences in metal transport due to the properties of three different fibers. Accurel PP 50/280 fibers, with a higher effective surface and smaller wall thickness, showed the highest efficiency for metal transport. Accurel PP Q3/2 exhibited intermediate efficiency but easier handling and, finally, Accurel PP S6/2 fibers, with a higher wall thickness, offered poorer efficiency but the highest stability and capability for metal speciation. Summarizing, selection of the polymeric support of HF-SLM is a key factor in their applicability of LPME for metals in natural waters.